2016
DOI: 10.1016/j.actatropica.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

High rate of unrecognized dengue virus infection in parts of the rainforest region of Nigeria

Abstract: Detection of DENV IgM in a cross-section of febrile patients using ELISA to determine sero-prevalence in the rain forest region in West Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 38 publications
5
23
0
Order By: Relevance
“…At the same time, major outbreaks of dengue have been reported in Dar es Salaam, including the 2014 DENV2 outbreak registering a case fatality rate of 4% ( Vairo et al, 2016 ). Dengue epidemics have also been reported from other parts of Tanzania ( Mboera et al, 2016 ), neighboring Kenya ( Brady et al, 2012 ), Mozambique ( Massangaie et al, 2016 ), as well as Angola ( Sharp et al, 2015 ), Sierra Leone ( de Araújo Lobo et al, 2016 ), Burkina Faso ( Ridde et al, 2016 ), and Nigeria ( Onoja et al, 2016 ) and several other parts of Sub-Saharan Africa ( L’Azou et al, 2015 ). Notably, in 2017, dengue outbreaks were reported from eight Sub-Saharan countries reaching an excess of 21,000 total cases.…”
Section: Evidence That Elimination Of Falciparum Malaria Coincides Wimentioning
confidence: 94%
See 1 more Smart Citation
“…At the same time, major outbreaks of dengue have been reported in Dar es Salaam, including the 2014 DENV2 outbreak registering a case fatality rate of 4% ( Vairo et al, 2016 ). Dengue epidemics have also been reported from other parts of Tanzania ( Mboera et al, 2016 ), neighboring Kenya ( Brady et al, 2012 ), Mozambique ( Massangaie et al, 2016 ), as well as Angola ( Sharp et al, 2015 ), Sierra Leone ( de Araújo Lobo et al, 2016 ), Burkina Faso ( Ridde et al, 2016 ), and Nigeria ( Onoja et al, 2016 ) and several other parts of Sub-Saharan Africa ( L’Azou et al, 2015 ). Notably, in 2017, dengue outbreaks were reported from eight Sub-Saharan countries reaching an excess of 21,000 total cases.…”
Section: Evidence That Elimination Of Falciparum Malaria Coincides Wimentioning
confidence: 94%
“…In 1977, Fagbami et al found that 45% of tested adults in Nigeria were seropositive for anti-DENV-2 antibodies, as evidenced by neutralizing antibodies ( Fagbami et al, 1977 ). In several African countries DENV transmission has been recognized primarily through diagnosis of travelers or stationed military personnel or through sero-prevalence population studies ( de Araújo Lobo et al, 2016 ; Onoja et al, 2016 ). It is mainly on the basis of such evidence that dengue is considered endemic to both East and West Africa ( Brady et al, 2012 ).…”
Section: Present and Past Prevalence Of Malaria Dengue And Populatimentioning
confidence: 99%
“…Many arboviruses circulate in Nigeria, yellow fever for example has caused large epidemics in the past ( Carey et al, 1972 ; Fagbami et al, 1976 ; Nasidi et al, 1989 , there are also serologic evidence of human infection with yellow fever, Dengue, West Nile and Zika virus ( Fagbami, 1979 ; Baba et al, 2013 , Onoja et al, 2016 ). Antibodies to Rift Valley fever have been demonstrated in sera of humans and animals in Nigeria ( Olaleye et al, 1996a ; b ).…”
Section: Introductionmentioning
confidence: 99%
“…These mosquitoes and hence arboviruses, continue to spread across the world even into areas that they never existed before [3], [34]. Nigeria, an endemic country for dengue fever, is currently experiencing several outbreaks of yellow fever [35], [36]. Despite these threats, entomological studies continue to rely on standard morphological keys for vector identification, at the expense of molecular methods like the PCR [24], [26], [37].…”
Section: Discussionmentioning
confidence: 99%